2023
DOI: 10.13005/bpj/2619
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Test of Active Compounds Natural Ingredients of Snail Mucus (Achatina fulica) Against BHK-21 Fibroblast Cells

Abstract: Snails are unpleasant yet beneficial. Rural people have used one to treat illnesses like toothache for years. We will test snail's mucus Achatina fulica's cytotoxic activity against Baby Hamster Kidney (BHK-21) fibroblast cells at 12.5%, 25%, 50%, 100% and its resistance to Phorpyromonas gingivalis, Fusobacterium nucleatum, E. Faecalis, and S. aureus using Microtetrazolium (MTT) assay. The test and comparison solution was incubated with 5x103/100 l cells in 96-well plates. 5 mg/mL MTT completed the solution's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…While high concentrations of A. fulica mucus exhibited increased cytotoxicity against BHK-21 fibroblast cells in vitro, lower doses demonstrated the ability to promote fibroblast proliferation, suggesting the snail mucus contains bioactive factors that can stimulate cell growth. 36 However. These preliminary results indicated that the mucus may have concentration-dependent cytotoxic and proliferative effects.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%
“…While high concentrations of A. fulica mucus exhibited increased cytotoxicity against BHK-21 fibroblast cells in vitro, lower doses demonstrated the ability to promote fibroblast proliferation, suggesting the snail mucus contains bioactive factors that can stimulate cell growth. 36 However. These preliminary results indicated that the mucus may have concentration-dependent cytotoxic and proliferative effects.…”
Section: Multifunctional Biomaterials With Diverse Biomedical and Cos...mentioning
confidence: 99%